Význam mediálnej výchovy v prvej dekáde 21. storočia - Slavíková, Nataša (Communication Today, 2025)
The paper is dealing with the meaning of media education in the fi rst decade of 21st century. The aim is not to give exhausting explanation of the whole problem but to show the effects of media contents and their relationship to context factors. It puts special attention to clarify the understanding how the moral context factors, age and style of presentation affect perception of audiovisual contents. It emphases the importance of six contexts such as: intention, motive, punishment, remorse, consequences and style of presentation. This study also focuses on new „Conception of Media Education in Lifelearnig Process“ which was approved by the Slovak Government on 16. Dec. 2009. Based on this document the importance of improving the level of the media literacy was stressed the whole society.